2017
DOI: 10.1167/iovs.16-20675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Complement C3 Levels With Primary Angle-Closure Glaucoma in Older Women

Abstract: Older women with PACG have lower plasma C3 levels, which were further demonstrated to be negatively associated with PACG severity. These findings suggest the involvement of C3 in the pathomechanisms of PACG in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…In our previous study, we also illustrated the association between oestrogen and the development of primary angle closure glaucoma (Li et al. ). As we are already aware, females have higher levels of oestrogen than males across all different age groups.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our previous study, we also illustrated the association between oestrogen and the development of primary angle closure glaucoma (Li et al. ). As we are already aware, females have higher levels of oestrogen than males across all different age groups.…”
Section: Discussionsupporting
confidence: 58%
“…There is also evidence to suggest that oestrogen is a protective factor against POAG in females and can also influence the levels of UA in the body (Li et al. ,). Overall, the difference between the genders in terms of the association between UA levels and POAG severity may be explained by the differences in oestrogen levels between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used to detect the C3 levels have been previously described in detail. 8 Control Subjects. A total of 600 subjects were recruited, of whom 134 normal subjects were later excluded from the study based on the inclusion criteria.…”
Section: Examinationmentioning
confidence: 99%
“…6,7 The complement system is the main component of the human native immune system, and it is involved in eye diseases. For example, Li et al 8 reported that people with primary angle-closure glaucoma have lower plasma complement component 3 (C3) levels, which were further demonstrated to be negatively associated with the severity of this condition 8 ; moreover, Yates et al 9 found that complement C3 is important in the pathogenesis of age-related macular degeneration. Complement C3 has the highest content and is the central component of the complement system, which interplays with other complement proteins and participates in the activation of the three pathways of complement activation: the classical, alternative, and lectin pathways.…”
mentioning
confidence: 99%
See 1 more Smart Citation